Analysis of Implementation Total Quality Management at Educational Institutions in Indonesia - Mercy Hosang; Deitje A. Katuuk; Viktory N.J. Rotty; Jeffry S.J. Lengkong (Tadbir : Jurnal Studi Manajemen Pendidikan, 2021)
The implementation of total quality management is applied to every educational institution as an effort to improve the quality of education. In this case, it is important to carry out management functions in each educational institution. This article discusses the implementation of total quality management in educational institutions to seek to improve the quality of education in achieving a quality standard in education. Every educational institution should show better quality and be able to compete. This is intended so that educational institutions continue to gain the trust of the public and stakeholders. To continue to get this, it must be improved continuously, both physically and non-physically. So as to make a quality educational institution and guaranteed quality. There are several main things that need to be considered in implementing total quality management in the world of education, namely: continuous quality improvement; determine quality standards, cultural change; changes in the organization; and maintain relationships with other agencies and customers and evaluate the system if anything is not appropriate